A prática do planejamento de ensino na educação de jovens e adultos - Nascimento, João Maria Pereira do (2010)
This work aims at analyzing EJA teaching planning process and its importance for teachers and students involved in it. The theories for this study have been based on some authors, such as: Arroyo (2005), Becker (2001), Brandão (2002), Gadotti (2007), Freire (2007), Libâneo (1994), Paludo (2001), among others. The methodology adopted was the qualitative and quantitative which present a better description and explanation of the social phenomena. The results has been obtained through a questionnaire applied to teachers who teach the second phase of elementary school of EJA in the Escola de Ensino Fundamental e Médio José Menino de Oliveira in the city of Solânea-PB. It has been observed that the researched teachers do not offer any opportunity for their students to collaborate in the choice of the subject contents and also the way they will be taught and evaluated. The students do not participate of the planning; even so, the educators claim to take into account the student s reality and interests what is a contradiction because the planning do not accomplish with the student s collaboration. However, the teachers demonstrate knowledge on what is planning with its importance and function to the success of teaching. Therefore, it is verified that the Escola Estadual de Ensino Fundamental e Médio José Menino de Oliveira does not take into consideration the planning, one of the most important tools in the teaching and learning process. We understood that through of a flexible, participative and continuous planning, it will be possible to detect the positive and negative aspects, and then to measure the quality of education available to young people and adults who take part of this educational modality.